Translating the Francophone Caribbean: Centering Black Production, Decentering Translation Practices - Nathan H Dize; Charly Verstraet (Studies in 20th & 21st Century Literature, 2023)
In her article, “A Tree as a Record: On Translating Mahagony by Edouard Glissant,” translator Betsy Wing recounts how Martinican writer Edouard Glissant expressed his disinclination to respond to translators’ questions and justified his intention by saying, “I wrote it once, now it’s your turn to write it” (124). According to Glissant, translating and writing are similar in nature. The art of translation therefore does not lie in the process of translating words into another language but in the skill to compose a text anew, that is to say to develop unique ways of ‘writing’ and therefore to deconstruct the idea of translation as a simple act of transferal. As such, this article considers various translators who have ‘written’ Caribbean texts anew. It will specifically look at three works from Black French-speaking Caribbean authors which were all translated into English, namely Patrick Chamoiseau, L’esclave vieil homme et le molosse (1997) translated by Linda Coverdale as Slave Old Man (2019); Gisèle Pineau’s La Grande drive des esprits (1993) translated by J. Michael Dash as The Drifting of Spritis (1999); and Yanick Lahens’s Tante Résia et les Dieux (1994) translated by Betty Wilson as Aunt Résia and the Spirits and Other Stories (2010). Comparing these translations side by side offers several points of interest: First, it places the race and gender of the author at the core of the translation. Chamoiseau, a Black Martinican man, was translated by Coverdale, a white woman from the United States; Lahens, a Black Haitian woman, by Wilson, a Black Jamaican woman; Pineau, a Black Guadeloupean woman, by Dash, a Trinidadian man. How does the race, gender, or ethnic background of the translator influence the process of translating Black-authored texts? In what ways does it affect the translation of Black experiences? Secondly, we examine various approaches to translating Caribbean creoles into English. For example, Coverdale deliberately keeps the Martinican French in her translation to emphasize the musicality of the text and the voice of the author over transparency and understanding. Similarly to Coverdale, Wilson’s translation preserves the Haitian Creole, which bears traces of orality, while also indicating filiations between Haitian Creole and creoles spoken in the Anglophone Caribbean in footnotes. Dash, on the other hand, elects to substitute one creole with another, the Guadeloupean with the Jamaican, allowing the text “to shove the reader around, to [to make them] feel unbalanced” (Dash, 30:09). If the approaches diverge between the translators, each of them views translation as a way to render a foreign text accessible, while simultaneously unsettling the reader’s world. Overall, this comparative analysis of the translations of Black authors from the Francophone Caribbean seeks to highlight a plurality of translation approaches centering Black cultural production while destabilizing the idea of a uniform translation practice.
Keywords: French Caribbean; Translation Studies; Patrick Chamoiseau; Gisèle Pineau; Yanick Lahens; Martinique Literature; Guadeloupe Literature; Haiti Literature